REDEMPTION OF THE MAIN CHARACTER IN THE NOVEL “THE KITE RUNNER” BY KHALED HOSSEINI (A GENETIC STRUCTURALISM APPROACH) - Sitti Aglitasia Merdekawati; Fachmi Alhadar; Nurfani Nurfani (Elite : English and Literature Journal, 2017)
AbstractThis research aims at to identify actions that reflect redemption. In addition, the other objective in it is to identify the factors cause redemption of the main character. The novel "The Kite Runner" features themes such as friendships, father and son relationships, even political and social class issues, as well as redemption itself. The researcher uses qualitative and descriptive methods. While the approach used is the approach of genetic structuralism to comprehend literary works thoroughly, ranging from the story structure in literary itself to the totality of life of the character which is inseparable from the historical social relationship of the author. This research also can not be separated from the use of library research in the form of previous researches or from internet sources, as well as reading comprehension to support in completing the data. Based on the research, the researcher finds there are three points from the first sub-issue, namely: the sacrifice of the main character for his father, and also to make amends and sin to Hassan, Sohrab adoption is a form of action from the main character to pay for his mistakes, And the struggle for his fear of returning to Kabul even championed Sohrab from the Talibans and also fight to stay alive so that they can return to America. While the second sub-problem has four points, including: the death of his mother Amir and also Hassan and his tragic family where such conditions depict Afghanistan in the inflation of Soviet troops and other communist parties. The sexual violence experienced by Hassan and Sohrab is reflected in the traditions and cultures that exist in Afghanistan in using the boys for their sexual needs. The betrayal of the main character, and the loyalty of Hassan, both of which also exist in the writer's circle as Hosseini also had a faithful Hazara whom he taught to write but the Hosseini’s family had to go abroad after the inflation and war. Hosseini finally went to America and left friends and other family in Kabul.AbstrakSkripsi ini bertujuan untuk mengidentifikasi aksi-aksi yang mencerminkan sebuah penebusan dosa. Selain itu, tujuan lainnya dalam penelitian ini adalah mengidentifikasi faktor-faktor penyebab penebusan dosa dari karakter utama. Novel “The Kite Runner” menampilkan berbagai tema seperti persahabatan, hubungan ayah dan anak, bahkan isu-isu politik dan kelas sosial, dan juga redemption itu sendiri. Peneliti menggunakan metode kualitatif dan deskriptif analisis. Sedangkan pendekatan yang digunakan adalah pendekatan strukturalisme genetik untuk memahami karya sastra secara menyeluruh, mulai dari struktur cerita dalam karya sastra itu sendiri hingga totalitas kehidupan dari karakter yang mana tidak terlepas dari hubungan sosial historis pengarangnya. Penelitian ini juga tidak terlepas dari penggunaan penelitian pustaka berupa penelitian-penelitian sebelumnya maupun dari sumber internet, serta pemahaman membaca untuk mendukung dalam melengkapi data tersebut. Berdasarkan penelitian ini, penulis menemukan ada tiga poin dari submasalah yang pertama, yaitu: pengorbanan dari the main character untuk ayahnya, dan juga untuk menebus kesalahan dan dosanya pada Hassan, adopsi pada Sohrab adalah bentuk tindakan dari the main character untuk membayar kesalahannya, dan perjuangan untuk melalui ketakutannya kembali ke Kabul bahkan memperjuangkan Sohrab dari para Taliban dan juga berjuang untuk tetap hidup agar mereka bisa kembali ke Amerika. Sedangkan submasalah yang kedua memiliki empat poin, diantaranya: kematian dari ibunya Amir dan juga Hassan dan keluarganya yang tragis dimana kondisi seperti itu menggambarkan Afghanistan dalam inflasi tentara Soviet dan partai komunis lainnya. Kekerasan seksual yang dialami oleh Hassan dan Sohrab yang mana hal tersebut tercermin dari tradisi dan budaya yang ada di Afghanistan sendiri dalam menggunakan anak-anak untuk kebutuhan seksual mereka. Pengkhianatan dari karakter utama, dan kesetiaan dari Hassan yang mana kedua hal tersebut juga ada di lingkungan penulis sebagaimana Hosseini juga memiliki seorang Hazara yang setia yang diajarkannya menulis namun keluarga Hosseini harus pergi ke luar negeri setelah terjadi inflasi dan perang. Hosseini akhirnya pergi ke Amerika dan meninggalkan teman-teman dan keluarga lainnya di Kabul.